(untitled) (Eurasian Journal of Philology Science and Education, 2019)
The article deals with the importance of Ganja, one of the ancient cities of Azerbaijan, in the sociopolitical history of the state. To this end, the author touched upon the events of the city reflecting the development of different periods of history and the proud freedom loving people. The theme of Ganja in Azerbaijani poetry is one of the most pressing topics facing modern literary criticism. The city of Ganja has been a symbol of national self-consciousness as a cultural and scientific center of our nation, as a symbol of freedom, independence and future of the country. That is why it is expedient to carry out scientific studies in the modern literary criticism and to bring it to the global arena when the national consciousness of the Azerbaijani people has increased and its sovereign rights have been strengthened. Based on all this, the article emphasizes the importance of continuing researches. The medieval sources of the ancient Ganja, which is a part of the research, confirm that the city has a truly glorious past. Although many historical events took place, Ganja was once again upgraded by the persistence of the people who had been revived and struggled with hardship. To clarify the significance of these statements, the article reviews some historical events. In addition to the article titled «Ganja’s Important Place in Socio-Political History of Azerbaijan», also names the cities (Tabriz, Baku, Ardabil, Maragha, Barda), symbolizing their names and playing a part in the political, social, cultural life of the people, information about them has been mentioned. Samples of poetic creativity of prominent poets were also given during the heroic cities of Azerbaijan.